Effect of Soy Protein Isolate (SPI) Concentration on Anthocyanin-Based Smart Indicator Labels from Purple Sweet Potato Waste - Rijanti Rahaju Maulani; Indrawan Cahyo Adilaksono; Angela Valentina Saputra; Rika Alfianny; Laras Putri Wigati; Aep Supriyadi; Nita Yuniati (PERTETA, 2026)
Indonesia has a high level of food waste, with up to 30% of the country’s total fruit production contributing to it. Smart packaging, such as that with anthocyanin based freshness indicator labels and Soy Protein Isolate (SPI), can help reduce waste by providing visual information about the product’s condition within the packaging. This research aims to determine the effect of SPI concentrations on the characteristics of anthocyanin-based smart packaging indicator labels extracted from purple sweet potato waste (Ipomoea batatas (L.) Lam). The indicator label was made using cornstarch (2.5%) as the matrix, glycerol as the plasticizer, and SPI as the crosslinking agent. The researchers employed a simple Completely Randomized Design with SPI concentration variations of 0%, 1%, 2%, 3%, and 4%. The researchers tested several parameters on the indicator labels, including pH sensitivity, color stability against storage temperature (4°C and 25°C), water absorption capacity, color reversibility, and biodegradability. The results indicate that adding SPI affects label characteristics, with 1% SPI concentration yielding the best performance. The 1% SPI concentration obtained the lowest color stability value at cold temperatures (∆E*ab = 5.15), the highest biodegradation rate (97.33% on day 4), the most varied color response to pH, and good physical durability of the label. Therefore, a 1% SPI concentration is recommended as the most effective formulation for an anthocyanin-based freshness indicator label.